Deciphering key factors in pathogen-suppressive microbiome assembly in the rhizosphere - Andargie, Yohannes Ebabuye; Lee, GyuDae; Jeong, Minsoo; Tagele, Setu Bazie; Shin, Jae-Ho (Frontiers in Plant Science, 2023)
In a plant-microbe symbiosis, the host plant plays a key role in promoting the association of beneficial microbes and maintaining microbiome homeostasis through microbe-associated molecular patterns (MAMPs). The associated microbes provide an additional layer of protection for plant immunity and help in nutrient acquisition. Despite identical MAMPs in pathogens and commensals, the plant distinguishes between them and promotes the enrichment of beneficial ones while defending against the pathogens. The rhizosphere is a narrow zone of soil surrounding living plant roots. Hence, various biotic and abiotic factors are involved in shaping the rhizosphere microbiome responsible for pathogen suppression. Efforts have been devoted to modifying the composition and structure of the rhizosphere microbiome. Nevertheless, systemic manipulation of the rhizosphere microbiome has been challenging, and predicting the resultant microbiome structure after an introduced change is difficult. This is due to the involvement of various factors that determine microbiome assembly and result in an increased complexity of microbial networks. Thus, a comprehensive analysis of critical factors that influence microbiome assembly in the rhizosphere will enable scientists to design intervention techniques to reshape the rhizosphere microbiome structure and functions systematically. In this review, we give highlights on fundamental concepts in soil suppressiveness and concisely explore studies on how plants monitor microbiome assembly and homeostasis. We then emphasize key factors that govern pathogen-suppressive microbiome assembly. We discuss how pathogen infection enhances plant immunity by employing a cry-for-help strategy and examine how domestication wipes out defensive genes in plants experiencing domestication syndrome. Additionally, we provide insights into how nutrient availability and pH determine pathogen suppression in the rhizosphere. We finally highlight up-to-date endeavors in rhizosphere microbiome manipulation to gain valuable insights into potential strategies by which microbiome structure could be reshaped to promote pathogen-suppressive soil development.